The role of Interleukin 6 inhibitors in therapy of severe COVID-19 (2020)
Cytokine storm syndrome (CSS) is a severe complication of inflammatory immune diseases or treatment of malignancies; it may also appear during the progression of COVID-19. CSS is caused by dysregulation of the synthesis of cytokines, including pro-inflammatory, regulatory, and antiinflammatory cytokines and chemokines, leading to pathologic activation of innate and adaptive (Th1 and Th17 mediated) immunity. Interleukin-6 (IL-6) plays an important role in the pathogenesis of CSS. The significant role of IL-6 in pathogenesis of COVID-19 was confirmed in a range of studies, which showed that the plasma concentration of IL-6 was increased in patients with severe COVID-19. Currently, IL-6 inhibitor therapeutics are not yet approved for the treatment of СOVID-19; however, these medicines, including tocilizumab (TCZ) are used off-label for the treatment of patients with severe СOVID-19, including life-threatening conditions. The role of IL-6 in the pathogenesis of CSS during COVID-19 is important however, a number of related issues are not yet clear. These issues include the indications for treatment with IL-6 inhibitors, as well as the estimation of risk associated with the disease, outcomes, treatment options, and adverse drug reactions. The development of personalized immunomodulatory therapy, with respect to the role of cytokines in pathogenesis, requires the studies that aimed to find other relevant therapeutic targets for the treatment of CSS in patients with COVID-19. These therapeutic targets include inhibition of IL-1, IL-6, TNFα, GM-CSF, IFNγ, IL-17, IL-18, and also activation of the complement system. The challenge of CSS in patients with COVID-19 is identifying the correct scientific targets and developing clinical trials aimed to evaluate the pathogenesis and treat immune-mediated inflammatory diseases (IMIDs). Hopefully, the significant efforts of scientists and physicians across the globe will improve the prognosis in COVID-19 patients and provide useful information on IMIDs required to support the struggle for treating potential viral outbreaks, and treatment of well-known IMIDs. Keywords: COVID-19, interleukin 6, cytokine storm syndrome 2. Introduction J